Analysing Bilingualism Utterances on Agatha Chelsea and Jerome Polin’s Podcast - Hermawan, Pradetya Fery; Sholihah, Nur Aisyh; Gomez, Octa Rwanda Rachman; Sarosa, Teguh (LingPoet: Journal of Linguistics and Literary Research, 2025)
Bilingualism is crucial in fostering global communication and cultural exchange. The study aims a) to analyze the bilingual utterances in a YouTube podcast of Agatha Chelsea and Jerome Polin, using Weinreich’s framework to understand the interaction of language use in digital courses; b) to highlight how bilingualism manifests in informal, public communication, and to provide insights into the implications of bilingualism for society and education. This study employs a qualitative descriptive approach, which aims to describe and explain a phenomenon or situation using qualitative data. The data were collected through a document analysis technique. It comprises of three steps namely identifying the documents, transcribing the data, and categorizing & coding the data. Then the data are analysed to determine the types of bilingualism in speech and the reason beyond the structure of the utterances. The result indicates that 80.6% of the bilingual utterances are subordinate bilingualism, while 19.4% are compound bilingualism. This ratio highlights the predominance of blending languages for clarity and inclusivity in digital media. This article contributes to the discourse on bilingual communication in digital platforms emphasizing the importance of bridging linguistic and cultural divides while enriching linguistic studies with real-world applications.